Stochastic modelling of the hybrid survival curve - Tan, Chong It (2016)
In this paper, building upon the idea of cross-sectional survival probabilities developed by Brouard (Espaces Popul Soc 2(14–15):157–168, 1986), we propose using stochastic models to study the evolution of a new type of survival curves called hybrid survival curve. We find that the three-factor survival model provides a better model fitting than the two-factor survival model. Furthermore, the three time-varying parameters are highly interpretable and their respective trends can be used as an indicator for the rectangularisation of survival curve. On top of that, we demonstrate how the time-varying parameters can be extrapolated into the future to obtain projected hybrid survival curves.